2021
DOI: 10.1186/s12985-021-01498-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus genotypes, herpes simplex, varicella zoster and cytomegalovirus in breast cancer patients

Abstract: Background The role of viruses as a cause of breast cancer (BC) has been significantly investigated in recent years. Human papillomavirus (HPV) has been detected in invasive breast carcinomas, while most studies have only focused on the detection of viral DNA, we aimed to examine the prevalence and genotypes of HPV among Iranian BC patients. We also examined the presence of herpes simplex-1 (HSV-1), herpes simplex-2 (HSV-2), varicella zoster virus (VZV), and cytomegalovirus (CMV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Studies that detect HCMV proteins in a high proportion of breast tumors also show >90% detection of HCMV DNA in these same tumors [ 19 , 41 , 42 , 43 ], with two studies also detecting mRNA for HCMV IE [ 42 , 43 ]. By contrast, some studies show a 40–80% positivity of HCMV DNA detection [ 19 , 48 , 49 , 50 ], while others report very few or no HCMV DNA-positive breast tumors [ 45 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. These differences could relate to the variability in serostatus for HCMV in the populations studied, which ranges from 60–100% [ 45 , 52 , 57 , 58 ]; however, in a population that is >90% HCMV seropositive, the detection of HCMV DNA in breast cancerous tissues is found to be as low as <20% [ 45 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that detect HCMV proteins in a high proportion of breast tumors also show >90% detection of HCMV DNA in these same tumors [ 19 , 41 , 42 , 43 ], with two studies also detecting mRNA for HCMV IE [ 42 , 43 ]. By contrast, some studies show a 40–80% positivity of HCMV DNA detection [ 19 , 48 , 49 , 50 ], while others report very few or no HCMV DNA-positive breast tumors [ 45 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. These differences could relate to the variability in serostatus for HCMV in the populations studied, which ranges from 60–100% [ 45 , 52 , 57 , 58 ]; however, in a population that is >90% HCMV seropositive, the detection of HCMV DNA in breast cancerous tissues is found to be as low as <20% [ 45 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication that MMTV has been involved with humans for millenia. New case control studies have confirmed that the prevalence of human papilloma viruses (HPVs) in breast cancer is significantly higher than in normal and benign breast tissue controls [ 4 , 5 ]. HPVs have been identified in circulating vesicles [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of tight relationships between different risk factors and central nervous system disorders, but the role of viral infections has drawn much attention 13,20‐22 . As symptoms of this disease are nonspecific, molecular analysis is essential to identify causative agents 23,24 . In this study, the prevalence of Herpesviridae and Picornaviridae was investigated in CSF of patients, suffering from meningitis.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 20 , 21 , 22 As symptoms of this disease are nonspecific, molecular analysis is essential to identify causative agents. 23 , 24 In this study, the prevalence of Herpesviridae and Picornaviridae was investigated in CSF of patients, suffering from meningitis.…”
Section: Discussionmentioning
confidence: 99%